INIBAP annual report 2004 - International Network for the Improvement of Banana and Plantain (2005)
Reconciling modernity and tradition to conserve diversity ; When West Africa meets Latin America ; The accidental pathogen ; Bringing back an old favourite, the capitalist way and INIBAP in brief.